Malaria Parasitemia during delivery - Ahmed, Sayed M.; Abd Al-Rhim, Somaya K; Mohamedani, Ahmed A.; Habour, Ali B.; Sadek, Ali A. (مجلة الجزيرة للعلوم الصحية; مجلد 1 عدد 1 (2004), 2004)
Objectives:  The aim of this study is to investigate the impact of plasmodium falciparum infection in parturient women in Central Sudan where malaria transmission is mesoendemic. The purpose of this paper is to find out the prevalenceof malaria parasitemia and the risk of anemia among parturient women and to suggest appropriate strategies to lower their prevalence rates. Methods:  This prospective study was conducted at Medani Teaching Hospital, Sudan a tertiary regional referral center, during the period January 1997 through to December 1997. All cases were admitted during labor to the delivery room and were clinically suspected to have malaria. History, examination and investigations were carried out on all patients. Results: The total number of patients enrolled in this study was 550, amounting to 14.9% of all women (N=3,687) who delivered during the study period. The prevalence of malaria parasitemia was 58.9% (N=550) while prevalence of anemia (defined as hemoglobulin   ….9.0 g/dl) was 24.1% the mean hemoglobuin levels in patients with positive and negative malaria parasitemia was 9.72 + 1.62 and 9.85 + 1.60 g/dl. Statistically the difference in the mean hemoglobulin level was not significant, t=0.879, A significant negative correlation between parasite count in maternal blood and hemoglobulin level of the mother, was observed, where r=0.121 (P=0.032). out of 17 (3.3%) patients who had used chloroquine tablets for prophylaxis, 11patients still had positive parasitemia. Although there was a higher parasite count in those 11 patients, statistically the difference was not significance where P< 0.05